Wild bird - Van Draanen, Wendelin (Alfred A. Knopf, 2017)
"When her behavior escalates out of control, fourteen-year-old Wren is taken away to a wilderness therapy camp where she is forced to develop new skills, including the courage to ask for help."--Provided by publisher.